2022
DOI: 10.1001/jamainternmed.2022.3178
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Pain Care Using Artificial Intelligence and Mobile Health Tools

Abstract: IMPORTANCECognitive behavioral therapy for chronic pain (CBT-CP) is a safe and effective alternative to opioid analgesics. Because CBT-CP requires multiple sessions and therapists are scarce, many patients have limited access or fail to complete treatment.OBJECTIVES To determine if a CBT-CP program that personalizes patient treatment using reinforcement learning, a field of artificial intelligence (AI), and interactive voice response (IVR) calls is noninferior to standard telephone CBT-CP and saves therapist t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…The five trials with non-inferiority designs established that there was no significant difference between standalone AI and clinicians (three trials) and between assisted unassisted clinicians (two trials). 8,12,1820 Hence, a total of 69 trials out of 84 (82·1%) have reported a positive result for their primary endpoint. A similar success rate was observed for the gastroenterology subset, with 27 of the 35 trials reporting significant improvement and one trial demonstrating noninferiority for an overall 80·0% success rate.…”
Section: Resultsmentioning
confidence: 99%
“…The five trials with non-inferiority designs established that there was no significant difference between standalone AI and clinicians (three trials) and between assisted unassisted clinicians (two trials). 8,12,1820 Hence, a total of 69 trials out of 84 (82·1%) have reported a positive result for their primary endpoint. A similar success rate was observed for the gastroenterology subset, with 27 of the 35 trials reporting significant improvement and one trial demonstrating noninferiority for an overall 80·0% success rate.…”
Section: Resultsmentioning
confidence: 99%
“…The most notable example is artificial intelligence, which is already demonstrating potential benefits for surgical systems, 66 in particular those for general surgery. [67][68][69] For prehabilitation interventions specifically, artificial intelligence could assist with intervention personalisation according to patient characteristics and preferences, enhancement of information provision and experience for potentially improved adherence, 70 predictive metrics to allow for early modulation of interventions when required, 71 and decision aids 72 for both clinicians and patients. In studies that have drawn broad media attention, artificial intelligence chatbots have shown high levels of quality and empathy when providing clinical solutions for patient issues, 73 and these could potentially enhance patient communication approaches within prehabilitation interventions before general surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another two comparative effectiveness studies aimed to confirm the feasibility and effectiveness of the mobile programs in the intervention treatment of depression and anxiety disorders (NCT02176226) and chronic pain (NCT02464449). The studies found that the introduction of ML and RL algorithms could facilitate the personalized formulation and adjustment of patient interventions, significantly improve patient compliance, and reduce the treatment time and labor costs compared with traditional treatment [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%